Validation of a cutoff point for the short version of the Depression Scale of the Center for Epidemiologic Studies in older Mexican adults - Aarón Salinas-Rodríguez; Betty Manrique-Espinoza; Gilberto Isaac Acosta-Castillo; Aurora Franco-Núñez; Óscar Rosas-Carrasco; Luis Miguel Gutiérrez-Robledo; Ana Luisa Sosa-Ortiz (Instituto Nacional de Salud Pública, 2014)
Objective. To identify a valid cutoff point associated with Center for Epidemiologic Studies, Depression Scale (CES-D) of seven items, which allows the classification of older adults according to presence/absence of clinically significant depressive symptoms. Materials and methods. Screening study with 229 older adults residing in two states of Mexico (Morelos and Tlaxcala), which were part of the sample from the National Survey of Health and Nutrition, 2012. We estimated the sensitivity and specificity associated with the selected cutoff points using the diagnostic criteria of ICD-10 (International Classification of Diseases, 10th revision) and DSM-IV (Diagnostic and Statistical Manual of Mental Disorders, fourth edition). Results. The cutoff point estimated was CES-D=5. According to the ICD-10 sensitivity and specificity were 83.3 and 90.2%, and ROC was 87%. Using DSM-IV, the values were 85, 83.2, and 84%, respectively. Conclusions. The short version of the CES-D can be used as a screening test to identify probable cases of older adults with clinically significant depressive symptoms.